Research on the dispute resulation mechanism of the HUI community in Northwest China (Journal of actual problems of jurisprudence, 2021)
The dispute resolution mechanism of the Muslim community in Northwest China, which is dominated by religious mediation, is greatly influenced by Islamic law. The author takes two disputes in Muslim community as examples to explore the characteristics and influencing factors of the dispute resolution mechanism under the background of Hui Chineseethnic minority culture. The study of the relationship between the informal path of religious mediation and the formal path of official dispute resolution mechanism brings us a new perspective to understand the religious dispute resolution mechanism of the Hui Muslim communities in Northwest China. In addition, what are the problems existing in the dispute settlement mechanism of the northwest Hui community? Why? This series of challenges and tests also belong to the research scope of this paper. Key words: Dispute Resolution; Mediation; Hui; Islamic Law; Northwest China.